2003
DOI: 10.1177/152660280301000512
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Graft Infection: Preliminary Results of an International Enquiry

Abstract: Infected endovascular grafts are an urgent problem that has been heretofore underestimated and will probably increase as follow-up lengthens. New techniques should be sought to expedite the diagnosis, and an international registry should be set up to provide validated data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
56
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 50 publications
0
56
0
Order By: Relevance
“…It has been shown that operating rooms can provide more sterile conditions than radiologic suites. 10 Fiorani et al 9 detected that 62% of infected EVARs were placed in a radiologic suite, however, not showing to be statistically significant. Another potential reason for infection proposed by the literature was embolization of a type II endoleak via a lumbar artery by thrombin injection 14 months after primary operation.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…It has been shown that operating rooms can provide more sterile conditions than radiologic suites. 10 Fiorani et al 9 detected that 62% of infected EVARs were placed in a radiologic suite, however, not showing to be statistically significant. Another potential reason for infection proposed by the literature was embolization of a type II endoleak via a lumbar artery by thrombin injection 14 months after primary operation.…”
Section: Discussionmentioning
confidence: 98%
“…It is widely known that the risk of an infection is apparently higher in patients who suffer from neoplastic disorders or who are receiving immunosuppressive therapy. 9 Fiorani et al 9 demonstrated an incidence of 22% of immunocompromised patients suffering from aortic graft infection in their collective. As it is mentioned previously, our patient was receiving immunosuppressive medication at the time of infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations